phot1 and phot2 mediate blue light-induced transient increases in cytosolic Ca(2+) differently in Arabidopsis leaves - Harada, Akiko (National Academy of Sciences, 2003)
Phototropins (phot1 and phot2) are blue light (BL) receptors that mediate phototropism, chloroplast movements, and stomatal opening in Arabidopsis thaliana. Physiological studies have suggested that Ca(2+) in the cytoplasm plays a pivotal role in these BL-induced responses. A phot1-mediated increase in cytosolic Ca(2+) was reported in deetiolated seedlings of A. thaliana; however, the contribution of phot2 remains unknown. We examined a BL-induced transient increase in cytosolic free Ca(2+) in leaves of transgenic A. thaliana of WT plants, phot1 and phot2 mutants, and phot1 phot2 double mutants expressing the Ca(2+)-sensitive luminescent protein aequorin. phot1 and phot2 had different photosensitivities: phot1 increased cytosolic Ca(2+) at lower fluence rates (0.1–50 μmol·m(-2)·s(-1)) and phot2 increased it at higher fluence rates (1–250 μmol·m(-2)·s(-1)). By using Ca(2+) channel blockers, Ca(2+) chelating agents, and inhibitors of phospholipase C, we further demonstrated that both phot1 and phot2 could induce Ca(2+) influx from the apoplast through the Ca(2+) channel in the plasma membrane, whereas phot2 alone induced phospholipase C-mediated phosphoinositide signaling, which might result in Ca(2+) release from internal Ca(2+) stores. These results suggest that phot1 and phot2 mediate the BL-induced increase in cytosolic free Ca(2+) differently.